2019
DOI: 10.1177/0883073819877790
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise Recommendation on Adolescents With Concussion

Abstract: We examined the effect of a noncontact, subsymptom exacerbation early exercise recommendation on recovery from sports-related concussion. Retrospective analysis of adolescents, 10-17 years old, with symptomatic concussion, within 30 days of injury was performed. Time to recovery was measured between the early exercise group and a comparison group. A total of 187 patients studied—112 in the exercise group and 75 in the comparison group; 55% were male (n = 103). The exercise group had a significantly longer dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…Ability to discriminate between concussed athletes and controls —Both computerised and paper-and-pencil cognitive tests differentiated athletes diagnosed with concussion from controls with medium to large effects during the first 24–48 hours post injury 36–42 Figure 4. depicts a forest plot of the acceptable and high-quality studies that compared overall SAC scores between acute concussed athletes and controls or baseline values.…”
Section: Resultsmentioning
confidence: 99%
“…Ability to discriminate between concussed athletes and controls —Both computerised and paper-and-pencil cognitive tests differentiated athletes diagnosed with concussion from controls with medium to large effects during the first 24–48 hours post injury 36–42 Figure 4. depicts a forest plot of the acceptable and high-quality studies that compared overall SAC scores between acute concussed athletes and controls or baseline values.…”
Section: Resultsmentioning
confidence: 99%
“…Further studies are needed to determine the outcomes of prescribing early PA, especially pertaining to patient adherence to PA recommendations and how an early introduction of PA may affect patient recovery given some studies have found contrasting results. 25 Symptom score at the time of initial visit was significantly associated with the level of PA recommendation, with higher symptom scores associated with decreased likelihood of recommending "light aerobic activity" or "noncontact PA." Symptom burden has often been cited as the most significant predictor for symptom recovery, emphasizing the importance of managing symptoms at the time of visit. 26 Recent studies support that a gradual return to physical activity could be safe and possibly help reduce the time to symptom resolution among pediatric patients who adhere to PA recommendations even if the patient is symptomatic.…”
Section: Discussionmentioning
confidence: 95%
“…Further studies are needed to determine the outcomes of prescribing early PA, especially pertaining to patient adherence to PA recommendations and how an early introduction of PA may affect patient recovery given some studies have found contrasting results. 25…”
Section: Discussionmentioning
confidence: 99%
“…For acute concussion, evidence concerning exercise included 20 studies: 7 RCTs, 41,[53][54][55][56][57][58] 8 prospective comparative studies, 42,43,[59][60][61][62][63][64] and 5 retrospective comparative studies 50,[65][66][67][68] in children, adolescents, and/or adults. Most studies involved adolescents.…”
Section: Acute Concussionmentioning
confidence: 99%